2009
DOI: 10.3846/1648-715x.2009.13.205-217
|View full text |Cite
|
Sign up to set email alerts
|

Cost Savings From Performance‐based Maintenance Contracting

Abstract: ABSTRACT. New procurement approaches combined with performance-based building approaches should reduce costs, but empirical qualitative and quantitative studies are lacking. Performance-based maintenance contracts give maintenance suppliers incentives to improve their way of working. Innovative, cost-effective solutions that meet the performance criteria can be achieved, especially if the principle of whole-life costing is being adopted. Indirect cost savings are expected as well. It enables maintenance contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 15 publications
1
44
0
1
Order By: Relevance
“…There are similar PBL success stories dealing with projects in the for-profit sector. For instance, one recent study of a major Dutch housing project showed that life cycle cost was reduced by 20 percent using a PBL approach (Straub, 2009).…”
Section: Background On Pblmentioning
confidence: 99%
“…There are similar PBL success stories dealing with projects in the for-profit sector. For instance, one recent study of a major Dutch housing project showed that life cycle cost was reduced by 20 percent using a PBL approach (Straub, 2009).…”
Section: Background On Pblmentioning
confidence: 99%
“…Performance-based contracting focuses the government's attention on a set of outcomes, allowing the contractors to determine the inputs and the process, and linking the outcomes to monetary rewards (Goldsmith and Eggers 2004;Heinrich 1999). While this mode of contracting may save costs (Straub 2009) and generate data for resource allocation decisions (Heinrich 1999), several problems have been noted. The performance standards are often not well-designed (Heinrich 1999), the sanctions are rarely executed in response to inadequate performance (Cohen and Eimicke 2008;Van Slyke 2007), and the democratic process of service delivery may be undermined (Chan and Rosenbloom 2010 Irrespective of the theoretical underpinnings of contractor performance measurement, the latter remains among "the most serious management challenges" facing public managers (Kelman 2002, 312).…”
Section: Introductionmentioning
confidence: 99%
“…Mossel and Straub's (2009) survey of tenants of social housing in the Netherlands also reveals the benefits of proper maintenance; these benefits include a sustained quality and an enhanced market value of the residential buildings. Opting for a performance-based maintenance contract, which is aimed towards meeting performance criteria set by clients, compared to the conventional competitive tendering also proved to be a cost-saving act, as it eased both indirect and direct costs (Straub 2009). In the meantime, previous studies have shown that an effective maintenance system will only become a reality if the stakeholders play their role in the maintenance system.…”
Section: Introductionmentioning
confidence: 99%